Effect of Bi3+ and Ti4+ substitution on PbNb2O6 piezoelectric ceramics. Issue 23 (1st December 2022) - Zhao, Xueming; Liu, Cheng; Zhang, Dainan; Huang, Da; Liu, Kui; Zhang, Huaiwu
Abstract: In this study, Pb1-2 x Bi2 x (Nb1- x Ti x )2 O6 (PBNT x, x  = 0.02–0.08) ceramics with tungsten bronze structure were prepared via the solid-state reaction method. Single orthorhombic ferroelectric phase was detected for all PBNT x ceramics. SEM results indicated fully densified morphology for the samples of x  ≥ 0.06. Optimal piezoelectric performance was obtained at the sample of x  = 0.08, whose piezoelectric constant ( d 33 ) reached to 92 pC/N and Curie temperature ( T c ) was up to 593 °C. A notably high electromechanical coupling coefficient ( k p ) greater than 0.6 was also obtained in this system. The improved piezoelectric performance indicated that Bi 3+ and Ti 4+ modified PbNb2 O6 system is promising for ultrasonic defect detection and transducer applications at high temperatures.